Treatment of tibial nonunion with bone defect using a heterotopic ossification as autologous bone graft: literature overview and case report - Schlumberger, Michael; Mayr, Raul; Koidl, Christian; Eichinger, Martin; Roth, Tobias (European journal of orthopaedic surgery & traumatology, 2018)
Introduction Nonunion after open fracture of the lower leg is a frequent complication with a prevalence of up to 40%. In cases with major bone defects, revision of the osteosynthesis with bone grafting is commonly performed. Until today, there is no report on treatment of a tibial nonunion with transplantation of a heterotopic ossification. Presentation of case We present a case of a 27-year-old male patient, who suffered from a paragliding accident with major injuries. An open fracture of the lower leg (Gustilo–Anderson IIIB) was initially treated with external fixation and vacuum-assisted closure, followed by reamed intramedullary nailing. The tibia resulted in a bone defect situation with nonunion. It was successfully treated with revision, fibular osteotomy and transplantation of a heterotopic ossification, harvested from the ipsilateral hip. Conclusion In special cases, autologous transplantation of a mature heterotopic ossification is an attractive bone graft option in treating nonunion defects.